Chemical modification of block copolymers based on 2-hydroxyethyl acrylate to obtain amphiphilic glycopolymers. (January 2015) - Muñoz-Bonilla, Alexandra; León, Orietta; Cerrada, María L.; Rodríguez-Hernández, Juan; Sánchez-Chaves, Manuel; Fernández-García, Marta
Graphical abstract: Highlights: Amphiphilic block copolymers are synthesized by ATRP. Their physico-chemical behaviors in solid state and in solution are analyzed. These copolymers are chemically modified to obtain glycopolymers. The glucopolymers are able to interact with Concanavalin A lectin. Abstract: The preparation of amphiphilic glycopolymers by chemical modification of di- and triblock copolymers based on 2-hydroxyethyl acrylate, HEA, and n -butyl acrylate, BA, is described in this manuscript. For that purpose, initially PBA- b -PHEA and PHEA- b -PBA- b -PHEA block copolymers were synthesized by controlled radical polymerization. After that, glycopolymers containing d -(+)-glucosamine or N -(4-aminobutyl)-d -gluconamide, NABG, were prepared by chemical modification of the HEA units. This process occurs in two consecutive steps: (1) an initial activation of the hydroxyl groups of the HEA units with highly reactive p -nitrophenyl carbonate groups and (2) the carbohydrate incorporation. In addition, the solid state and solution behaviors of PBA- b -PHEA and PHEA- b -PBA- b -PHEA di- and triblock copolymers are described by using differential scanning calorimetry, X-ray diffraction, atomic force microscopy and dynamic light scattering. The results have been compared with those previously obtained with methacrylate derivatives. Finally, the resulting water soluble glycopolymers have been exposed to lectins and the aggregation capacity and the selectivity have been also evaluated.